2015
DOI: 10.1099/ijs.0.000198
|View full text |Cite
|
Sign up to set email alerts
|

Halobacillus andaensis sp. nov., a moderately halophilic bacterium isolated from saline and alkaline soil

Abstract: A Gram-stain-positive, endospore-forming, moderately halophilic bacterial strain, NEAU-ST10-40 T , was isolated from a saline and alkaline soil in Anda City, China. It was strictly aerobic, rod-shaped and motile by peritrichous flagella. It formed light yellow colonies and grew at NaCl concentrations of 3-15 % (w/v) (optimum, 8 %, w/v), at pH 7.0-9.0 (optimum, pH 8.0) and at 4-60 8C (optimum, 30 8C). It contained meso-diaminopimelic acid in the cell-wall peptidoglycan. Phylogenetic analysis based on 16S rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Also, UPF0118 exhibited Na + (Li + )/H + antiport activity mainly under alkaline conditions from pH 8.0 to 9.5 (Fig. 7), which may be related to the adaptation of its host to the extremophilic saline-alkaline conditions, since strain NEAU-ST10–40 T is a moderate halophile with the optimum growth at the 8% (w/v) NaCl concentrations and at pH 8.039.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, UPF0118 exhibited Na + (Li + )/H + antiport activity mainly under alkaline conditions from pH 8.0 to 9.5 (Fig. 7), which may be related to the adaptation of its host to the extremophilic saline-alkaline conditions, since strain NEAU-ST10–40 T is a moderate halophile with the optimum growth at the 8% (w/v) NaCl concentrations and at pH 8.039.…”
Section: Discussionmentioning
confidence: 95%
“…In our recent study39, strain NEAU-ST10-40 T , a moderate halophile isolated from Na 2 CO 3 -type saline and alkaline soils in Anda City, China was identified to represent a novel species Halobacillus, Halobacillus andaensis , with the growth range of NaCl concentrations of 3–15% (w/v) (optimum, 8%, w/v) and pH 7.0–9.0 (optimum, pH 8.0), and thus this novel halophilic strain from unique saline-alkaline conditions could have developed sophisticated mechanisms to maintain its intracellular steady osmotic and ionic state. Since almost all halophilic microorganisms have the ability to expel Na + from the interior of the cells using Na + (Li + )/H + antiporters4041, it is very likely that important (even novel) Na + (Li + )/H + antiporter genes exist in this novel strain NEAU-ST10-40 T , a moderate halophile which can tolerate up to 15% (w/v) NaCl.…”
mentioning
confidence: 92%
“…The strains and plasmids related to this study are shown in Table 1 . H. andaensis NEAU-ST10-40 T was cultured in a modified S–G liquid medium with the composition as described by Wang et al (2015) . E. coli strain KNabc (Δ nhaA Δ nhaB Δ chaA ; Nozaki et al, 1996 ) and its transformants were cultured in the LBK medium composed of 1.0% tryptone, 0.5% yeast extract, and 87 mM KCl as described by Karpel et al (1988) or KCl-removed LBO (“O” stands for 0 mM KCl) medium solely consisting of 1.0% tryptone and 0.5% yeast extract.…”
Section: Methodsmentioning
confidence: 99%
“…That has been partially established by the recent report by Meng et al (2017) that a pair of functionally unknown homologous DUF1538 family proteins from the moderate halophile Halomonas zhaodongensis function as a novel two-component Na + (Li + , K + )/H + antiporter. As the type strain of a novel species of Halobacillus andaensis ( Wang et al, 2015 ), NEAU-ST10-40 T is a moderate halophile isolated from unique Na 2 CO 3 -type saline and alkaline conditions, which can grow at the range of NaCl concentrations of 0.5–2.5 M (optimum, 1.4 M) and pH 7.0–9.0 (optimum, pH 8.0). Therefore, this novel halophile may have evolved profound mechanisms for the stability of its intracellular osmotic and ionic state.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Halobacillus , proposed by Spring et al in 1996 [1] , contains isolates from diverse sources such salt lakes [1] , [2] , [3] , solar salterns [4] , [5] , [6] , [7] , saline soil [8] , [9] , [10] , deep sea methane seeps [11] , sea anemone [12] and mangrove ecosystems [13] , [14] . Many of this group׳s members are of industrial importance for their production of halotolerant extracellular enzymes [15] , [16] .…”
Section: Datamentioning
confidence: 99%